2023
DOI: 10.7759/cureus.35070
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy Versus Stenting for the Treatment of Patients With Carotid Artery Stenosis: An Updated Systematic Review and Meta-Analysis

Abstract: Carotid endarterectomy (CEA) is a surgical procedure that treats the narrowed carotid arteries, which may be narrowed by atherosclerosis. Stenting is the insertion of a wire mesh scaffold into the narrowed portion of the carotid artery to keep it open by preventing blood from clotting. Using the study done over 10 years back as a point of reference, this study will seek an update on an assessment comparing CEA and stenting in studies carried out between 2015 and to date. The PICOS (population, intervention, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Patients who underwent CEA had higher rates of myocardial infarction, and those who had stenting had higher rates of stroke [25]. A recent systematic review and meta-analysis by Vasavada et al evaluated the literature since the CREST trial was published and showed similar findings; CEA resulted in decreased rates of stroke and composite rates of stroke or death, but higher rates of myocardial infarction compared with CAS [26 ▪ ]. Specifically for patients with CAS after cervical radiation, studies have continued to show that CEA offers improved long term outcomes regarding risk of cerebrovascular events and restenosis [27].…”
Section: Treatment Of Carotid Artery Stenosis In Head and Neck Cancermentioning
confidence: 96%
“…Patients who underwent CEA had higher rates of myocardial infarction, and those who had stenting had higher rates of stroke [25]. A recent systematic review and meta-analysis by Vasavada et al evaluated the literature since the CREST trial was published and showed similar findings; CEA resulted in decreased rates of stroke and composite rates of stroke or death, but higher rates of myocardial infarction compared with CAS [26 ▪ ]. Specifically for patients with CAS after cervical radiation, studies have continued to show that CEA offers improved long term outcomes regarding risk of cerebrovascular events and restenosis [27].…”
Section: Treatment Of Carotid Artery Stenosis In Head and Neck Cancermentioning
confidence: 96%
“…effects of stents and CEA are similar (Vasavada et al, 2023). To fight their related risks, the new variants of drug-eluting stents were developed, that are thinner and made of biocompatible polymers.…”
Section: Introductionmentioning
confidence: 99%
“…2 Vasavada et al presented an update on carotid intervention with systematic review and meta-analysis offering a current perspective on the comparative effectiveness of CEA and CAS. 3 The Wallstent is a stent usually crafted from a thin and flexible biocompatible metal alloy, commonly stainless steel or nitinol (a nickel-titanium alloy). It is designed as a meshlike structure with high flexibility, allowing it to adapt to the shape of the vessel or passage it is placed in.…”
mentioning
confidence: 99%